Approaches to integrate land-use and transport planning. Analysing the political dimension of integrative planning - Levin-Keitel, Meike; Reeker, Irina Kim (Raumforschung und Raumordnung | Spatial Research and Planning, 2021)
Assuming that mobility behaviour of citizens can be partially influenced by certain spatial structures, the integration of land-use and transport planning seems to be a key aspect of a transition towards sustainable mobility. Such an integrated planning approach is characterised, for example, by increased cross-sectoral interaction, softened institutionalised boundaries between the two sectors of land-use and transport planning as well as cross-sectorally shared goals. However, this often-articulated claim for integration remains unclear in its implementation. Hence, this article presents a conceptual framework within the three dimensions of policy, polity and politics to grasp what integration comprises in its different aspects. The two German cities of Dortmund and Hanover serve as case studies. It appears that informal interaction (politics) between the two sectors acts as a necessary precondition whereas true political will and shared targets (policy) are needed to really initiate the process towards integration. Ultimately, an approach is fully integrated if the institutional design (polity) is adapted in terms of hierarchical coordination and largely removed sectoral boundaries.